Strategi Peningkatan Bisnis Fashion Hijab Deymirr Store di Kalangan Gen Z - Gunawan Gunawan; Miska Nur Syahada (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study analyzes business growth strategies for hijab fashion at Deymirr Store among Generation Z. It highlights the importance of quality control, customer satisfaction, and effective marketing strategies in navigating the dynamic hijab fashion industry. By utilizing market segmentation, digital marketing, and product innovation approaches, the research aims to identify key factors that can enhance the competitiveness of Deymirr Store.The results show that the use of social media platforms such as Instagram and TikTok plays a significant role in increasing brand awareness among Gen Z. Additionally, differentiation strategies through the use of premium-quality materials and trend-conscious designs are major factors in attracting customers. The study also reveals challenges such as stock instability during high demand periods and the need for accurate financial projections to support business growth.